Semantic Analysis of Contextual Items in WhatsApp Conversations - Sanju Febrio Saragih; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the semantic role of contextual items—emojis, abbreviations, and discourse markers—in shaping meaning within WhatsApp conversations. Using a qualitative content analysis method, data were collected from naturally occurring chats among users aged 18 to 35. The findings show that emojis function as emotional amplifiers or softeners, abbreviations facilitate rapid and informal exchanges, and discourse markers manage tone, coherence, and politeness strategies. These elements work collaboratively to perform speech acts such as apologizing, refusing, and building interpersonal rapport. Based on Speech Act Theory and Relevance Theory, this study concludes that meaning in WhatsApp communication is co-constructed through interaction and social context. The research contributes to studies in digital discourse, semantics, and sociolinguistics, particularly within the Indonesian context.